Is globalisation good for Sub-Saharan Africa? Threats and Opportunities - Anthony Njau Ntuli (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
This paper reviews the effects globalisation has on the economic prosperity of sub-Saharan Africa, on a global information economy context, and in particular, the threats that globalisation has brought about as well as, the opportunities that are likely to emerge because of it. The fundamental shift in the nature of the global economy backed up by viable strategies, acting within the realities of globalisation and information economy open-up new windows for latecomers, and enables them converge the gap by capitalising on the opportunities it offers. In order to narrow the gap created by globalisation, disadvantaged regions such as the SSA need to create 'spaces of globalisation' by re-orienting their geographic areas, thus taking full advantage of the information economy by developing information infrastructure and knowledge workers in their respective countries. This re-orientation should also include the development of a comprehensive strategic vision that enhances the potential of globalisation and the information economy within the geographic space. Due to the rapid change in the general process of industrialisation and export-led industrial growth in particular, determinates of competitiveness are not resource endowed but knowledge and skill driven. Empirical evidence has shown a close correlation between economic growth and export expansion proving that the fastest growing economies are those, which position themselves as favourable business partners, endowed with investment friendly locations, and rapidly expanding export. A country's ability to export processed or highvalued products doubles when it emerges as knowledge-intensive and skill-intensive in its share of manufactured exports in a given region. This works possible with increased access ability to learning and technology. Thus, the analysis underscores the importance in production diversification and structural improvement in order to absorb the benefits global information economy offers.
Keywords: 330; Globalisierung; Zentralafrika